2021
DOI: 10.1039/d1dt02003j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, antimicrobial and antibiofilm activity, and molecular docking analysis of NHC precursors and their Ag-NHC complexes

Abstract: A series of novel silver(i)-NHC complexes are synthesized and characterized. The anticandidal activity of some complexes was found to be similar to that of Flucanozol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…All methyl carbon peaks of salts were observed at 20.7 ppm for. These values agree with reported data for similar N-heterocyclic carbenes [27]. The FT-IR, 1 H NMR, and 13 C{ 1 H} NMR spectra are presented in the details in the Supplementary Files (Figures S1, S6).…”
Section: Characterization Of N-heterocyclic Carbene Saltssupporting
confidence: 89%
“…All methyl carbon peaks of salts were observed at 20.7 ppm for. These values agree with reported data for similar N-heterocyclic carbenes [27]. The FT-IR, 1 H NMR, and 13 C{ 1 H} NMR spectra are presented in the details in the Supplementary Files (Figures S1, S6).…”
Section: Characterization Of N-heterocyclic Carbene Saltssupporting
confidence: 89%
“…Üstün et al [11] showed the antibiofilm activities of the Ag(I)-NHC compounds they synthesized on grampositive and negative bacteria and fungal strains. Celik et al [19] In their study, they reported that Ag(I)-NHC compounds inhibited the biofilm formation of grampositive and gram-negative bacteria and yeast strains by 32-84% while degrading mature biofilms by 14-66%.…”
Section: Resultsmentioning
confidence: 99%
“…The biofilm inhibition value at SubMIC was calculated with Eq. [11] Biofilm inhibition ( % ) = { ( Ac − As ) / Ac } 100 where As and Ac are the absorbance of sample and control, respectively. This test was performed in triplicate and the mean (n = 3) was taken.…”
Section: Reduction In Biofilm Formationmentioning
confidence: 99%
“…Ag(I)‐NHC complexes ( 2a–d ) were synthesized under argon gas atmosphere and according to the literature. [ 31 ]…”
Section: Methodsmentioning
confidence: 99%